Distribution system analysis and automation - Gers, Juan M. (The Institution of Engineering and Technology, 2013)
The following topics are dealt with: smart grid; distribution automation functions; short circuit calculation; reliability; volt/VAR control; harmonic analysis; power distribution protection and interoperability concepts.